A case study of a mesospheric bore event observed with an all-sky airglow imager at Tirunelveli (8.7°N) - Narayanan, V. Lakshmi; Gurubaran, S.; Emperumal, K. (My University, 2009)
[1] A prominent front separating bright and dark regions of all-sky airglow images was recorded on the night of 22/23 March 2007, at the low-latitude Indian station Tirunelveli (8.7°N, 77.8°E) and is attributed to a mesospheric bore. With the help of complementary wind information from the colocated MF radar and temperature and density data from the SABER instrument onboard TIMED mission, the parameters of the bore are calculated and discussed. Because the observed wind at the emission altitude was orthogonal to the direction of bore propagation, Doppler ducting was not likely to support the bore. The analysis that makes use of the square of buoyancy frequency profiles reveals a thermal duct that would provide favorable conditions for the propagation of the bore. This is the first report of a mesospheric bore event from the Indian sector.
Keywords: Mesospheric bore; MF radar; Density; Airglow imager; Tirunelveli